2020
DOI: 10.1016/j.msard.2020.102154
|View full text |Cite|
|
Sign up to set email alerts
|

A new look at an old test: Normative data of the symbol digit modalities test –Oral version

Abstract: Background: The Symbol Digit Modalities Tests (SDMT) is the most sensitive measure to multiple sclerosis (MS)related cognitive dysfunction. However, existing normative data has been under scrutiny. Specifically, they are outdated, do not take into account gender, and are poorly stratified by education. More importantly, there exists no oral only version norms, which is typical administration among individuals with MS. Objective: The present investigation aimed to develop updated normative data of the oral vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 27 publications
(29 reference statements)
0
35
0
Order By: Relevance
“…SDMT scores were lower at baseline among men. Furthermore, normative scores on the oral SDMT in healthy volunteers are significantly (p < 0.001) lower for men than women (Strober et al, 2020). The previously published primary analysis of SUNBEAM did not show a significant variation in ozanimod efficacy by gender, based on ARR, new/enlarging T2 lesion count, or GdE lesion count (Comi et al, 2019).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…SDMT scores were lower at baseline among men. Furthermore, normative scores on the oral SDMT in healthy volunteers are significantly (p < 0.001) lower for men than women (Strober et al, 2020). The previously published primary analysis of SUNBEAM did not show a significant variation in ozanimod efficacy by gender, based on ARR, new/enlarging T2 lesion count, or GdE lesion count (Comi et al, 2019).…”
Section: Discussionmentioning
confidence: 76%
“…Normative scores in a (non-MS) general community population <40 years of age ranged from 50-58 for written responses and 59-66 for oral responses (Sheridan et al, 2006). Scores tend to decrease with age and are influenced by education and gender (Sheridan et al, 2006;Strober et al, 2020). Updated normative values for the oral SDMT range from 55-68 in men aged 18-54 years, and 60-70 in women in the same age range (Strober et al, 2020).…”
Section: Assessment Of Cps With Sdmtmentioning
confidence: 99%
See 1 more Smart Citation
“…The SDMT (37) is a symbol substitution test that examines processing speed and attention and is reported as the most sensitive test for MS cognitive problems (38) . Age-, education-, and gender-adjusted norms are available (39) , and these will be used to de ne cognitive impairment (for study-eligibility) as: scoring 1.5 SDs or more below the normative reference-value.…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…In the current study, the SDM test showed strong betweenperson (α = .90-.92) and within-person reliability (α = .90). Furthermore, it has shown strong 2-week retest reliability (r = .74), convergent and discriminant validity, with scores of measures of different constructs [71][72][73].…”
Section: Processing Speedmentioning
confidence: 99%